Islamic nationhood and colonial Indonesia : the umma below the winds - Laffan, Michael Francis, 1969- (RoutledgeCurzon, 2003)
This book argues that Indonesian nationalism rested on Islamic ecumenism heightened by colonial rule and the pilgrimage.
Keywords: Nationalism -- Indonesia -- History.; Islam and politics -- Indonesia -- History.; Ummah (Islam) -- Indonesia -- History.; Southeast Asians -- Saudi Arabia -- Hejaz -- History.; Southeast Asians -- Egypt -- Cairo -- History.; Indonesia -- Politics and government -- 1798-1942.; Nationalisme -- Indonésie -- Histoire.; Ummah (Islam) -- Indonésie -- Histoire.; Asiatiques du Sud-Est -- Arabie saoudite -- Hedjaz -- Histoire.; Asiatiques du Sud-Est -- Égypte -- Le Caire -- Histoire.; Indonésie -- Politique et gouvernement -- 1798-1942.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; Islam and politics; Nationalism; Politics and government; Southeast Asians; Ummah (Islam); Egypt -- Cairo; Indonesia; Saudi Arabia -- Hejaz; 1798-1942; Electronic books.; History